ei2αei2αcos(2α)+isin(2α)=ei(α+α)=eiα+iα=eiαeiα=(cos(α)+isin(α))(cos(α)+isin(α))=cos(α)cos(α)+icos(α)sin(α)+isin(α)cos(α)+i2sin(α)sin(α)=cos(α)cos(α)+icos(α)sin(α)+isin(α)cos(α)+(−1)sin(α)sin(α)=cos(α)cos(α)+icos(α)sin(α)+isin(α)cos(α)−sin(α)sin(α)=cos2(α)+icos(α)sin(α)+isin(α)cos(α)−sin2(α)=(cos2(α)−sin2(α))+i(cos(α)sin(α)+sin(α)cos(α))=(cos2(α)−sin2(α))+i(sin(α)cos(α)+sin(α)cos(α))=(cos2(α)−sin2(α))+i(2sin(α)cos(α))=(cos2(α)−sin2(α))+i(2sin(α)cos(α))For z∈C and q∈C,if z=qthen Re(z)=Re(q) and Im(z)=Im(q)thus,Im(cos(2α)+isin(2α))sin(2α)=Im((cos2(α)−sin2(α))+i(2sin(α)cos(α)))=2sin(α)cos(α)Q.E.D.